Enhancing Collaboration Skills and Student Learning Outcomes Through the Implementation of an Ethnoscience-Based Common Knowledge Construction Model (CKCM) with Podcasts - Munawarah, Sinta Al; Yamtinah, Sri; Utomo, Suryadi Budi; Wiyarsi, Antuni; Widarti, Hayuni Retno; Shidiq, Ari Syahidul (Journal of Education Reseach and Evaluation, 2024)
Responding to the challenges of 21st-century education, educators must implement innovative approaches to optimize student learning. Recognizing the importance of ethnoscience as a cultural lens that enriches traditional knowledge and constructivist learning, facilitated through the Common Knowledge Construction Model (CKCM), is essential to encourage the development of ideas. Using podcasts as a learning medium is increasingly promising in improving understanding of the material. This research analyzes the impact of ethnoscience-based CKCM with podcasts on chemical bonds. This type of research is quantitative, using a quasi-experimental design with a posttest-only control group. The sample in this study was 61 students, and it was taken using random sampling techniques. The data collection method uses tests. The data collection instrument uses test question sheets. The data analysis technique uses inferential statistical analysis. The research results show no significant difference in applying ethnoscience-based CKCM and podcasts on chemical bonds. While there are no striking differences, these findings provide avenues for future research, exploring differences in student engagement, podcast content development, and variations in teaching methodology. This exploration can contribute valuable educational insights to the ongoing discourse regarding effective strategies, providing benefits to educators and researchers aiming to improve learning outcomes in science education.